2020
DOI: 10.17221/152/2019-swr
|View full text |Cite
|
Sign up to set email alerts
|

Potentially toxic metals and metalloids in surface water intended for human consumption and other uses in the Mantaro River watershed, Peru

Abstract: The concentration of Cu, Fe, Pb, Zn and As in the surface water intended for human consumption and other uses in the Mantaro River basin were analysed using multivariate methods. The water samples were collected from seven water bodies in the Junín region in June 2019, in the low discharge period. In each body of water, a sector with six sampling sites was established. The Cu, Fe, Pb, Zn and As contents were determined by the flame atomic absorption spectrophotometry method. The correlation analysis revealed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
7
1
1
Order By: Relevance
“…Cr>Mn>Ni>Zn>Cu>Pb, Cr>Pb>Zn>Cu>Mn>Ni, and Zn>Cr>Cu>Mn>Ni>Pb in all the groundwater and surface water sources, respectively. The results of present study were found in agreement with the previous studies conducted in mining areas of Hunan province, China (Gong et al 2014), in Dabaoshan of Guangdong province, China , in Palma, Spain (Rodellas et al 2014), in Brajrajnagar of Jharsuguda district, India (Sahoo and Khaosh 2020), in Taojian, China (Chen et al 2019), in Maracas at Port of Spain (Santana et al 2020), and in Mantaro, Peru (Custodio et al 2020), respectively as shown in (Table S3).…”
Section: Discussionsupporting
confidence: 92%
“…Cr>Mn>Ni>Zn>Cu>Pb, Cr>Pb>Zn>Cu>Mn>Ni, and Zn>Cr>Cu>Mn>Ni>Pb in all the groundwater and surface water sources, respectively. The results of present study were found in agreement with the previous studies conducted in mining areas of Hunan province, China (Gong et al 2014), in Dabaoshan of Guangdong province, China , in Palma, Spain (Rodellas et al 2014), in Brajrajnagar of Jharsuguda district, India (Sahoo and Khaosh 2020), in Taojian, China (Chen et al 2019), in Maracas at Port of Spain (Santana et al 2020), and in Mantaro, Peru (Custodio et al 2020), respectively as shown in (Table S3).…”
Section: Discussionsupporting
confidence: 92%
“…In the Mantaro River, the main river in the basin, high concentrations of heavy metals and metalloids have been recorded that exceed the environmental quality standards for water in the Peruvian standard and the threshold values of WHO and US EPA. However, in this study the concentrations of these metallic contaminants are lower in most of the sectors evaluated than those registered by Custodio et al (2020) [30] in this same river basin in April 2019, where activities were regular.…”
Section: Analysis and Distribution Of Heavy Metals And Arsenic In Surface Watercontrasting
confidence: 74%
“…Table 1 shows the mean and standard deviation of heavy metals and arsenic recorded in surface water of the Mantaro River basin during 2020, compared to data recorded in 2019 [30]. The results from both years show similar behavior of the rivers as a function of their average concentration of the elements evaluated.…”
Section: Analysis and Distribution Of Heavy Metals And Arsenic In Surface Watermentioning
confidence: 86%
“…Additional to the grey clustering, the r-Pearson linear correlation coefficient between each parameter and overall water quality index, determined by the clustering coefficient belonging to the first grey class, was obtained to achieve a better understanding of the dynamics behind water pollution and establishing predictive relationships. Though specific correlation significance intervals are mostly subjective and depend on the size of the data and the science branch where it is applied, in this study the intervals were the ones used by [13] where a strong absolute correlation is higher than 0.76; a moderate correlation is higher than 0.51, a weak correlation is higher than 0.26 and below that point correlation can be neglected.…”
Section: B Pearson Correlation Testmentioning
confidence: 99%